HUBUNGAN AKTIVITAS FISIK DAN STRES DENGAN GANGGUAN SIKLUS MENSTRUASI PADA SANTRIWATI PONDOK PESANTREN DAYAH DARUZZAHIDIN KABUPATEN ACEH BESAR - Putri Ilham Sari (Cahaya Ilmu Bangsa Institute, 2024)
World Health Organization (WHO) in 2019, determined that 1/5 of the world's population consists of adolescents. The population of Asia Pacific is 60% of the world's population and 1/5 are adolescents. The International Coercion on Population Development (ICPD) defines reproductive health as the end result a state of physical, mental, and social well-being and not merely the absence of disease and infirmity in all matters related to the reproductive system, functions and processes. Purpose: Determine the relationship between physical activity, stress and menstrual cycle disorders in female students at Dayah Daruzzahidin Islamic boarding school, Aceh Besar Regency. Research Method: Analytical with a Cross Sectional approach. All populations were sampled, namely 60 people. Research Results: Based on the analysis and discussion that has been described previously, a conclusion can be drawn about the results of the study as follows: Based on the p-value of 0.024 <0.05, have relationship between physical activity and menstrual cycle disorders in female students at Dayah Daruzzahidin Islamic boarding school, Aceh Besar Regency. Based on the p-value of 0.000 <0.05, have a relationship between stress and menstrual cycle disorders in female students at Dayah Daruzzahidin Islamic boarding school, Aceh Besar Regency. Conclusion: physical fatigue and stress have a significant relationship with menstrual cycle disorders, some female students tired from studying from morning to night, the higher the stress due to fatigue from studying felt by students, the worse their menstrual cycle will be.